The Use of Najwa Tsurayya Dictionary in Increasing Arabic Vocabulary Memorization for Class VII Students at MTs Al Irsyad Tengaran 7 Batu City/ استخدام قاموس نجوى الثرايا في زيادة حفظ المفردات العربية لطلبة الصف السابع في المدرسة الثانوية الإرشاد تنجاران السابع مدينة باتو - Muhammad Alwan Nursuhaida; Nurul Murtadho (Universitas Negeri Malang, 2022)
This article is the result of research with the aim of describing the implementation of vocabulary learning with Najwa Al-Thoraya's Pocket Dictionary in seventh-grade students of Al-Irshad Tangaran Seventh Secondary School, Batu City. The researcher uses experiments, and it is in two sessions, each of which consists of; Planning, action, observation and evaluation. The results of the research show that there is data that learning Arabic using Najwa Al-Thoraya dictionary is effective in memorizing vocabulary, and this is evidenced by vocabulary test scores that exceed KKM (minimum standards). There are several drawbacks in this educational activity, such as limited learning time, ability of each student, etc. However, these drawbacks can be overcome. In conclusion, Najwa Al-Thoraya's dictionary increases the vocabulary of seventh-grade students.هذه المقالة هي نتيجة البحث بهدف وصف تنفيذ تعلم المفردات بقاموس الجيب نجوى الثرايا في طلاب الصف السابع د المدرسة الثانوية الإرشاد تنجاران السابع مدينة باتو. الباحث يستخدم البحث التجارب ويكون في دورتين، كل منهما تتكون من؛ التخطيط، العمل، الملاحظة والتقويم. تظهر نتائج البحث بأن هناك بيانات تفيد بأن تعلم اللغة العربية باستخدام قاموس نجوى الثرايا فعالية في حفظ المفردات، ويتضح ذلك من خلال درجات اختبار المفردات التي تتجاوز KKM (معايير الحد الأدنى). وهناك عدة العوائق في هذا النشاط التعليمي ، مثل وقت التعلم المحدود ، وقدرة كل طالب ، وما إلى ذلك. ومع ذلك، يمكن التحليل على هذه العوائق. الخلاصة أن قاموس نجوى الثرايا يكثر مفردات طلاب الصف السابع.